Role of the Al-doping and epitaxial strain in the multiferroic behavior of TbMnO3 bulk and thin films (2017)
The Ph.D. thesis reports on the experimental investigation of the structure and physical properties of the perovskite-type multiferroic TbMnO3 when doped with aluminum ions in different atomic positions. The study is carried out both in bulk form and thin films. In thin film form, the material is additionally submitted to compressive/tensile epitaxial strain. Multiferroic compounds are a novel class of material, which feature both spontaneous electrical polarization and magnetization, within the same phase. Multiferroics are rare in nature and many research groups around the world have directed their efforts to the discovery/synthesis of new multiferroics. The main interest in this class of materials is the possibility of observing high magnetoelectric response in them. A strong coupling between the electrical and magnetic orders in these materials would open a wide spectrum of potential applications in spintronics and/or non-volatile 4-state memories. Nevertheless, the reported couplings up to now are still too weak, which hampers the practical applications. In this regard, plausible ways to enhance the response of the material are the use of an appropriate dopant (chemical pressure), the application of an external pressure or epitaxial strain. Whereas the theoretical aspects of the fundamental mechanisms related to the appearance of multiferroicity in some materials has experimented considerable advance over the last few years, the discovery or creation of new systems with enhanced magneto(-di) electric response represent a challenge for disciplines such as solid state physics and materials sciences. The main objective of this thesis is to study the role of chemical doping and epitaxial strain on the structure and physical behavior of a multiferroic material. TbMnO3 was chosen as test multiferroic because its spontaneous electrical polarization, due to a spiral spin ordering, gives rise to a large magnetoelectric coupling. Furthermore, large strain effects are to be expected in such system because of the subtle balance between the magnetic interactions and its large magnetic frustration. For these reasons, a detailed study on the structure and properties of Al-doped TbMnO3, both in bulk and thin film form, has been conducted in this thesis. We motivate the interest of fabricating thin films of TbMnO3 because this allows one to visualize the effect compressive/tensile strain on the magnetic response of this challenging multiferroic. In chapter 1, we introduce the multiferroic and magnetoelectric materials and their interest from the fundamental and from the applications point of view, as well as the compound subject of this thesis, TbMnO3. The synthesis of bulk TbMnO3 as well as the growth and study of thin films are introduced in chapter 2. In the same chapter, we present the experimental tools used for the characterization of the samples including high-resolution X-ray diffraction X-ray photoelectron spectroscopy, atomic force microscopy, electrical, magnetic and dielectric characterization techniques. In chapter 3, we present and discuss the results achieved on undoped and Al-doped bulk TbMnO3 samples synthesized by solid state reaction. In particular, the XRD patterns show that the Al ions are effectively entering in the crystalline structure of TbMnO3. A clear distinction between de doping at the Tb and Mn places is observed. The Rietved refinement of the XRD patterns corroborates this assertion. The effect of the Al-doping is also evident from the results of the (di-)electrical, and magnetic measurements. Indeed, the Al-doping leads to a decrease in the value of the electrical resistance and consequently to an increase in the value of the conductance. Impedance analysis allowed us to separate the different contributions to the dielectric response and revealed Debye-like relaxation mechanisms. As to the magnetic response, it was shown that the dominant magnetic interactions in the TbMnO3 bulk material films are antiferromagnetic. Nevertheless, the doping with Al ions suggests that ferromagnetic interactions are present in the bulk samples below the Neel temperature, evidenced by a splitting between the field-cooled (FC) and zero-field-cooled (ZFC) magnetization curves. Although the origin of the ferromagnetic in this multiferroic is controversially discussed, it is generally accepted that the lattice distortion caused by the Al-doping is behind the effect. The thermal characterization of the bulk samples show that the system has a quite high Seebeck coefficient and a relatively low thermal conductivity, which would make the TbMnO3 multiferroic a promissory thermoelectric material. Nevertheless, the low electrical conductivity at low temperatures conduces to a low figure of merit, which certainly hinders the practical applications of this material. The growth, structure and properties of the TbMnO3 thin films grown under compressive/tensile strain on single crystals of atomically flat MgO and SrTiO3 substrates is reported in chapter 4. Films with different orientations are obtained on each substrate material and for different growing parameters. In spite of this, all films show well-defined ferromagnetic signal below the Curie temperature, which also varies according the substrate and growing parameters chosen. By optimizing the growing parameters, thin films can be epitaxialy grown on (001)-oriented SrTiO3 substrates. The films (50-150 nm) show orthorhombic distortion and are partially relaxed. Thus, it is probable that a strained and a relaxed part coexist in the films with thicknesses within the range previously mentioned. The main results in this chapter can be summarized as follows: a. the successful stabilization of undoped and Al-doped TbMnO3 thin films under compressive strain on SrTiO3 substrates when sputtering is used as physical deposition technique. b. the magnetic measurements performed on the films show that the dominant magnetic interactions in the thin films are antiferromagnetic, similar to the bulk material, but that ferromagnetic interactions are present in the undoped films below the Neel temperature. The magnetic response of the films is clearly improved upon Al-doping, which corroborates the central role of the chemical pressure in the magnetic behavior of the studied system. The orthorhombic distortion seems to be a good candidate to explain the origin of the induced ferromagnetism in the films. However, some reports found in the literature on the concerned system suggest apart from the structural distortion, the presence of domain walls can equally causes the ferromagnetism in the TbMnO3 films. Although it is evident that further work is necessary in order to acquire a deeper insight into the multiferroic behavior of TbMnO3, the results presented in this thesis contain valuable information that will contribute to extend the general knowledge on the TbMnO3 multiferroic existent in the literature on the thematic.